Conflicting values: ecosystem services and invasive tree management - Ian A. Dickie; Brett M. Bennett; Larry E. Burrows; Martin A. Nuñez; Duane A. Peltzer; Annabel Porté; David M. Richardson; Marcel Rejmánek; Philip W. Rundel; Brian W. van Wilgen (Biological Invasions, 2014)

Soil drainage and phosphorus depletion contribute to retrogressive succession along a New Zealand chronosequence - David A. Coomes; Warren A. Bentley; Andrew J. Tanentzap; Larry E. Burrows (Plant and Soil, 2013)

Higher relative performance at low soil nitrogen and moisture predicts field distribution of nitrogen-fixing plants - Adrian Monks; Ellen Cieraad; Larry Burrows; Susan Walker (Plant and Soil, 2012)

Secondary woody vegetation patterns in New Zealand's South Island dryland zone - Susan Walker; Nigel King; Adrian Monks; Sophie Williams; Larry Burrows; Ellen Cieraad; Colin Meurk; Jacob McC Overton; Robbie Price; Mark Smale (New Zealand Journal of Botany, 2009)
Can New Zealand's indigenous dryland ecosystems be rehabilitated by facilitating inherent successional tendencies to enhance development of indigenous‐dominated and often woody communities in the long term? Here, we describe the geographic distribution of woody communities of New Zealand's South Island drylands to generate hypotheses about successional trajectories to future vegetation states. Presences and absences of woody species in 3880 vegetation plots collated from past surveys were used to predict species potential distributions across drylands. Separate models and spatial predictions were built for each of four classes of woody richness, which were used as surrogates for successional stages. Woody species richness increased significantly from grassland to shrubland and from shrubland to forest cover, and trends in species traits also suggest richness class was related with successional stage. Indigenous woody species outnumbered exotic species in all richness classes. Assuming richness classes represent temporal progressions, our results suggest relatively homogeneous early‐successional woody associations succeed to a divergent array of woody associations in different environments. Growth forms of species in our predicted associations suggest transitions from grassland to tall, tree‐rich forests in northern and coastal drylands, and to liane‐rich open or lightcanopied shrubland, woodland, or low forest in more severe inland environments. These putative communities are novel in species composition but physiognomically broadly similar to pre‐settlement analogues. Especially in severe inland environments, unassisted transitions from grassland to indigenousdominated late‐successional woody communities may depend on the exclusion of tall exotic trees, Scotch broom, and gorse in early succession.

Tree fern trunks facilitate seedling regeneration in a productive lowland temperate rain forest - Aurora Gaxiola; Larry E. Burrows; David A. Coomes (Oecologia, 2008)

The potential for long‐term persistence of forest fragments on Tongatapu, a large island in western Polynesia - Susan K. Wiser; Donald R. Drake; Larry E. Burrows; William R. Sykes (Journal of Biogeography, 2002)
Aim We describe compositional variation among forest fragments on Tongatapu in terms of successional status and site conditions. We then examine two factors that directly influence the potential for long‐term persistence of these fragments – tree regeneration and alien invasion. Location Tongatapu is the largest (261 km 2 ), most densely inhabited (population 67,000) island in the Kingdom of Tonga, western Polynesia. Inhabited for 3000 years, it is now more than 90% deforested. Methods We mapped land cover from 1990 aerial photographs and sampled forest fragments and selected regenerating (late bush fallow) stands. Composition data from forest fragments were analysed with cluster analysis and ordination, and then an environmental framework was constructed to allow floristic comparisons between these and late bush fallow stands. We analysed size‐structures of tree populations to evaluate regeneration. Distribution patterns of aliens introduced by Polynesian settlers (ancient introductions) and after European contact (modern introductions), were compared. Growth forms were compared to determine whether aliens are qualitatively distinct from the native forest fragment flora. Correlation analysis and hierarchical regression determined whether factors such as disturbance, soil fertility, species richness, fragment size, and distance to forest margin, which influence invasion patterns elsewhere, were important on Tongatapu. Results Forest fragments occupy 3.2% of the land area; regenerating `bush fallow' stands occupy 7.9%. We recorded 209 vascular plant species, half of which were trees or shrubs; other growth forms were, in decreasing order of importance, forbs, lianes and vines, graminoids and ferns. Eight per cent of the species were ancient introductions and 33% were modern introductions. Forest fragments were classed into four types: interior, coastal, Excoecaria coastal swamp and Inocarpus coastal swamp – the latter two unknown elsewhere in Tonga. Successional tree species are important components of interior and coastal forests. Most frequent species in forest fragments also occur in late bush fallow plots. In forest fragments, six of the nine most frequent tree species have abundant juveniles available to replace adults; three are successional and their regeneration was not observed under closed canopies. Most (thirty‐three of forty‐five) less common tree species were more frequent as juveniles than adults. Invasion patterns differ among forest types. Late bush fallow stands support the highest alien cover, mostly trees and shrubs. Among forest fragments, interior forest is the most invaded and Excoecaria swamp forest is least invaded. Main conclusions Forest fragments on Tongatapu are small, highly disturbed and spatially disjunct. Composition relates, at least in part, to proximity to the coast, soil drainage and soil type and composition of most non‐successional tree species appears to be being maintained. Compositional integrity is threatened by selective harvesting and invasive aliens. Modern introductions are more abundant than ancient introductions in late bush fallow areas and may pre‐empt their establishment. Significantly, even small, degraded forest patches harbour an important component of native biodiversity.